Critical causes of accident under reporting in Malaysia construction industry - Lim, Andy Say Wai (2007)
All construction employers in Malaysia are required to have an injury reporting system that ensures all workplace parties are aware of how to report a work-related injury to the authorities and to the appropriate persons designated by the employer. Occupational Safety and Health (Notification of Accident, Dangerous Occurrence, Occupational Poisoning And Occupational Disease) Regulations 2004 is stated in Occupational Safety and Health Act 1994. Part II of this regulation stated the conditions when the notification and reporting of accident and dangerous occurrence arising out of or in connection with work should be made. Reporting of Injuries, Diseases and Dangerous Occurrences Regulations 1995 (RIDDOR) requires the reporting of work-related accidents, diseases and dangerous occurrences. The information enables the enforcing authorities to identify where and how risks arise and to investigate serious accidents. The aim of the study is to identify the critical causes of accident under reporting in Malaysia construction industry. The study was done within the Malaysian construction industry and a questionnaire is designed. The methodology of the study involves document studies of existing accident reporting procedure, questionnaire survey, and face to face interview with safety officer. Data was analyzed using statistical method included frequency and average index analysis. At the end of the thesis, a list of critical causes of accident under-reporting in Malaysia construction industry is identified and recommendations are given as a summary of this research. This will be useful by construction companies in improving their accident reporting system.